Age measurements on antarctic rocks (Queen Maud Land) - Deutsch, Marie Sarah; Picciotto, Edgardo; Reinharz, Max (1961)
WE wish to report here the results of absolute age measurements carried out on rocks from the Sör-Rondane Mountains. These mountains, extending from 23°E. to 28°E. in Queen Maud Land, were explored in 1958 in the course of the Belgian Antarctic Expedition led by Gaston de Gerlache1. Preliminary accounts of the geology and of the petrography of this region have been published2,3 already. © 1961 Nature Publishing Group. SCOPUS: ar.j info:eu-repo/semantics/published